Sovietisation of Schools in the autum in 1940: ideological constraints from teachers, bolshevis indoctrination,compain of eadult education, selebration of boshevik a coup d’état in in Schools of Šakiai County; (1) - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2014)
The subject of the article is the phenomena and facts of the Sovietisation of general education schools in the first months of 1940–1941, which are still largely unreported in the historiography. The peak of the aggressive indoctrination of teachers, pupils and other people more or less connected with educational institutions with primitive Bolshevik ideas was reached during the celebrations of the 23rd anniversary of the Great October Socialist Revolution of 1917 on 6–8 November 1940. The article is mainly based on the files of the Lithuanian Central State Archives (LCSA), which have hardly been used in the historiography, as well as on the materials of the Lithuanian Special Archives (LSA), and on other archival, historiographical and the author’s personal sources.